2011
DOI: 10.1186/1756-0500-4-429
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations due to rotavirus gastroenteritis in Catalonia, Spain, 2003-2008

Abstract: BackgroundRotavirus is the most common cause of severe gastroenteritis among young children in Spain and worldwide. We evaluated hospitalizations due to community and hospital-acquired rotavirus gastroenteritis (RVGE) and estimated related costs in children under 5 years old in Catalonia, Spain.ResultsWe analyzed hospital discharge data from the Catalan Health Services regarding hospital admissions coded as infectious gastroenteritis in children under 5 for the period 2003-2008. In order to estimate admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
(40 reference statements)
4
12
0
8
Order By: Relevance
“…We found in this study the presence of an annual seasonality with spikes in the months of June or August depending on the region, but, both confirmed the results found in the literature with the largest rotavirus disease incidence in the cold and dry months 11,12,13,20,21 .…”
Section: Discussion and Final Considerationssupporting
confidence: 81%
“…We found in this study the presence of an annual seasonality with spikes in the months of June or August depending on the region, but, both confirmed the results found in the literature with the largest rotavirus disease incidence in the cold and dry months 11,12,13,20,21 .…”
Section: Discussion and Final Considerationssupporting
confidence: 81%
“…Studies have shown that rotavirus gastroenteritis is more frequent in the autumn and winter months [16,17]. Similarly, we found that rotavirus gastroenteritis was more frequent (77.5%) between October and March.…”
Section: Discussionsupporting
confidence: 66%
“…[24][25][26][27] The trend described in CLM resembles that noted for Spain as a whole. [10][11][12][13] 29,30 This means a 73% annual reduction of direct costs of RH. In European regions of low to moderate commercialization of the new vaccine, the reduction of IR under 2 y of age was 25-36% when comparing the periods 2008-11 and 2004-06, 31 similar to the decrease in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these drugs are not subsidized by the government, recent studies have estimated a significant decrease in rotavirus hospitalizations in Spain since their use became more widespread in 2008. [10][11][12][13] Other industrialized countries have already shown a reduction in hospital admissions after 1 to 2 y of a complete immunization schedule, [14][15][16] with the vaccine remaining effective up to 3 y after the last dose. 17,18 The aim of our research is to describe the burden borne by hospitals due to community-acquired rotavirus in CLM and its …”
Section: Introductionmentioning
confidence: 99%